Exiles : a novel - Coile, Mason, 1968- (G.P. Putnam's Sons, 2025)
"A terrifying locked-room mystery from the author of William--this time set on a remote outpost on Mars. The human crew sent to prepare the first colony on Mars arrives to find the new base half-destroyed and the three robots sent to set it up in disarray--the machines have formed alliances, chosen their own names, and picked up some disturbing beliefs. Each must be interrogated. But one of them is missing. In this barren, hostile landscape where even machines have nightmares, the astronauts will need to examine all the stories--especially their own--to get to the truth. Exiles is a terrifying, taut, one-sitting read, and Mason Coile once again blends science fiction and psychological horror to engage some of humanity's deepest questions."--